Opportunities and Challenges in Understanding Atherosclerosis by Human Biospecimen Studies - Elishaev, Maria; Hodonsky, Chani J.; Ghosh, Saikat Kumar B.; Finn, Aloke V.; von Scheidt, Moritz; Wang, Ying (Frontiers in Cardiovascular Medicine, 2022)
Over the last few years, new high-throughput biotechnologies and bioinformatic methods are revolutionizing our way of deep profiling tissue specimens at the molecular levels. These recent innovations provide opportunities to advance our understanding of atherosclerosis using human lesions aborted during autopsies and cardiac surgeries. Studies on human lesions have been focusing on understanding the relationship between molecules in the lesions with tissue morphology, genetic risk of atherosclerosis, and future adverse cardiovascular events. This review will highlight ways to utilize human atherosclerotic lesions in translational research by work from large cardiovascular biobanks to tissue registries. We will also discuss the opportunities and challenges of working with human atherosclerotic lesions in the era of next-generation sequencing.